A first-order segregation phenomenon in fluid-immersed granular systems - Nair, Prapanch; Torres Cisneros, Luis Armando; Windows-Yule, Christopher Robert Kit; Agrawal, Nikhil; Roy, Shantanu; Pöschel, Thorsten (Powder Technology, 2020)
A vast majority of widely accepted granular segregation mechanisms are attributed to dynamic phenomena such as percolation, kinetic sieving, convection-induced segregation, condensation, inertia and granular temperature gradients. We distinguish the ballistics of the particles from such dynamic and material properties and show that the former is a dominant mechanism in the segregation of particles sedimented in a container. We first perform granular sedimentation experiments with glass beads in water that exhibit size-segregation of bidisperse grains. We then show through simulations using a simple, first-order model that the ballistics of the particles alone is sufficient to qualitatively predict this segregation.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Bidisperse system; Granular packing; Granular segregation; Overdamped phenomena

Can Minkowski tensors of a simply connected porous microstructure characterize its permeability? - Nair, Prapanch; Mühlbauer, Sebastian; Roy, Shantanu; Pöschel, Thorsten (Physics of Fluids, 2021)
We show that the permeability of periodic simply connected porous media can be reliably predicted from the Minkowski tensors (MTs) describing the pore microstructure geometry. To this end, we consider a large number of two-dimensional simulations of flow through periodic unit cells containing complex-shaped obstacles. The prediction is achieved by training a deep neural network using the simulation data with the MT elements as attributes. The obtained predictions allow for the conclusion that MTs of the pore microstructure contain sufficient information to characterize the permeability, although the functional relation between the MTs and the permeability could be complex to determine.
CRIS-Team WoS Importer:2021-05-14

Capillary viscous flow and melting dynamics: Coupled simulations for additive manufacturing applications - Blank, Michael; Nair, Prapanch; Pöschel, Thorsten (International Journal of Heat and Mass Transfer, 2019)
The rate of melting of a solid and the rate of deformation of the resulting melt due to capillary forces are comparable in additive manufacturing applications. This dynamic structural change of a melting solid is extremely challenging to study experimentally. Using meshless numerical simulations we show the influence of the flow of the melt on the heat transfer and resulting phase change. We introduce an accurate and robust Incompressible Smoothed Particle Hydrodynamics (ISPH) method to simulate melting of solids and the ensuing fluid-solid interaction. We present validations for the heat transfer across the free surface and the melting interface evolution, separately. We then present two applications for this coupled multiphysics simulation method — the study of rounding of an arbitrarily shaped particle during melting and the non-linear structural evolution of three spheres undergoing agglomeration. In both the studies we use realistic transport and thermal properties for the materials so as to demonstrate readiness of the method for solving engineering problems in additive manufacturing.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Additive manufacturing; Incompressible Smoothed Particle Hydrodynamics; Latent heat; Melting dynamics; Phase change

Coupled Simulation of Deformable Bodies and ISPH Fluids for Secondary Bone Healing - Aburumman, Nadine; Müller, Patric; Nair, Prapanch; Pöschel, Thorsten (Eurographics technical report series, 2017)
We propose a new scheme for the two-way coupling of incompressible fluids and deformable bodies, where we focus on a medical application; in particular, secondary bone healing. Our method allows for accurate simulation and visualisation of the secondary bone healing process, which is used to optimise clinical treatment of bone fractures. In our simulation, the soft tissues are simulated as elastic materials using Strain Based Dynamics (SBD), and fluid is simulated using Incompressible Smoothed Particle Hydrodynamics (ISPH). The interaction model we propose works with any type of deformation technique as long as the object surface is represented by a polygonal mesh and the fluid by Lagrangian particles.

Dynamic capillary phenomena using Incompressible SPH - Nair, Prapanch; Pöschel, Thorsten (Chemical Engineering Science, 2017)
Grid based fluid simulation methods are not able to solve complex non-linear dynamics like the rupture of a dynamic liquid bridge between freely colliding solids–an exemplary scenario of capillary forces competing with inertial forces in engineering applications–using a monolithic formulation for the solid and liquid phases present. We introduce a new Incompressible Smoothed Particle Hydrodynamics method for simulating three dimensional fluid-solid interaction flows with capillary (wetting and surface tension) effects at free surfaces. This meshless approach presents significant advantages over grid based approaches in terms of being monolithic and in handling interaction with free solids. The method is validated for accuracy and stability in dynamic scenarios involving surface tension and wetting. We then present three dimensional simulations of crown forming instability following the splash of a liquid drop, and the rupture of a liquid bridge between two colliding solid spheres, to show the method’s advantages in the study of dynamic micromechanical phenomena involving capillary flows.

Isotropy of sphere packings in a cylindrical confinement - Agrawal, Nikhil; Nair, Prapanch; Pöschel, Thorsten; Roy, Shantanu (Chemical Engineering Journal, 2019)
The underlying structure in apparently “randomly-packed” packed beds is a subject of topical interest, particularly in the context of deep processing, such as deep hydrodesulfurization. Packed beds typically exhibit “packing defects”; for instance, surface abnormalities such as a slope, a bump (convex surface), a hollow (concave surface), or even donut-shaped rings on the top surface of a packed bed. While these defects are observed at the top free surface of the packed bed, there are concerns that this may continue to propagate down the height, and in turn, cause local flow variations and differential wetting, which affect reactor performance, catalyst life, and formation of local hot spots. These defects come because of different protocols that are followed for packing particles, which are mainly developed out of empiricism since the physics of granular flow in confinements (such as a vertical cylindrical reactor vessel) is as yet not well understood. Earlier work on the structure of packed beds relates only to the spatial distribution of voidage, and not on how the particles are arranged with respect to each other in the reactor. This work is an attempt in that direction. We present first the use of Sequential Ballistic Deposition (SBD) algorithm to model the packing process itself, i.e., how the method of packing (modeled in this work through some simple protocols) yields a certain structure of the bed. Second, we show the use of Voronoi tessellation and the use of two of the Minkowski tensors (the Volume Moment Tensor and the Surface Orientation Tensor) to characterize the packed bed structure. Further analysis is presented which shows that we are able to fingerprint the packed bed formed through different packing methods, hence creating a link between the two.
CRIS-Team Scopus Importer:2019-10-15
Keywords: isotropy; Minkowski tensors; Sequential Ballistic Deposition; Trickle bed; Voidage distribution; Voronoi tessellation

ISPH–PBD: coupled simulation of incompressible fluids and deformable bodies - Abu Rumman, Nadine; Nair, Prapanch; Müller, Patric; Barthe, Loïc; Vanderhaeghe, David (Visual Computer, 2020)
We present an efficient and stable method for simulating the two-way coupling of incompressible fluids and deformable bodies. In our method, the fluid is represented by particles, and simulated using divergence-free incompressible smoothed-particle hydrodynamics (ISPH). The deformable bodies are represented by polygonal meshes, where the elastic deformations are simulated using a position-based dynamics scheme. Our technique enforces incompressibility on the fluid using divergence-free constraints on the velocity field, while it effectively simulates the physical features of deformable bodies. Most current ISPH methods are struggling with the issue of free-surface boundary conditions. We handle this problem by introducing a novel free-surface formulation, where our free-surface model obviates the need to identify the surface particles. For the interaction between the fluid and the deformable solids, we model the forces that both phases, fluid and solid, exert upon each other. We demonstrate that our approach effectively handles complex coupling scenarios between fluids and thin deformable shells or highly deformable solids, and produces plausible results.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Deformable bodies; Fluids; ISPH; PBD; Thin shells

Janssen effect in dynamic particulate systems - Windows-Yule, C. R. K.; Mühlbauer, Sebastian; Torres Cisneros, Luis Armando; Nair, Prapanch; Marzulli, Valentina; Pöschel, Thorsten (Physical Review E, 2019)
The Janssen model of stress redistribution within laterally bounded particulate assemblies is a longstanding and valuable theoretical framework, widely used in the design of industrial systems. However, the model relies on the assumption of a static packing of particles and has never been tested in a truly dynamic regime nor for a constraining system whose geometry is dynamically altered. In this paper, we explore the pressure distributions of granular beds housed within a container possessing a laterally mobile sidewall, allowing the depth, height, and cross-sectional areas of the systems studied to be dynamically altered, thus, inducing particle rearrangements and flow in the particulate system constrained thereby. We demonstrate that the systems studied can be successfully described by the Janssen model across a wide range of system expansion rates, including those for which liquidlike flow is clearly observed and propose an extension to the model allowing for an improved characterization of constrained dynamic systems.
CRIS-Team WoS Importer:2019-09-06

Simulations of gas-liquid compressible-incompressible systems using SPH - Nair, Prapanch; Tomar, Gaurav (Computers & Fluids, 2019)
Gas bubbles immersed in a liquid and flowing through a large pressure gradient undergo volumetric deformation in addition to possible deviatoric deformation. While the high density liquid phase can be assumed to be an incompressible fluid, the gas phase needs to be modeled as a compressible fluid for such bubble flow problems. The Rayleigh-Plesset (RP) equation describes such a bubble undergoing volumetric deformation due to changes in pressure in the ambient incompressible fluid in the presence of capillary force at its boundary, assuming axisymmetric dynamics. We propose a compressible-incompressible coupling of Smoothed Particle Hydrodynamics (SPH) and validate this coupling against the RP model in two dimensions. This study complements the SPH simulations of a different class of compressible-incompressible systems where an outer compressible phase affects the dynamics of an inner incompressible phase. For different density ratios, a sinusoidal pressure variation is applied to the ambient incompressible liquid and the response of the bubble in terms of volumetric deformation is observed and compared with the solutions of the axisymmetric RP equation. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-05-28

Structural changes in wet granular matter due to drainage - Nair, Prapanch; Pöschel, Thorsten (EPJ Web of Conferences, 2017)
Unsaturated wet granular media are usually modelled using force laws based on analytical and empirical results of liquid bridge forces between pairs of grains. These models make ad-hoc assumptions on the liquid volume present in the bridges and its distribution. The force between grains and rupture criterion of the bridge are a function of this assumed volume of liquid, in addition to other parameters like contact angle of the liquid, geometry of the grains and the inter grain distance. To study the initial volume and morphology of liquid bridges, hydrodynamic simulation of dynamic effects leading to formation of liquid bridges at grain scale are indispensable. We use a Smoothed Particle Hydrodynamics algorithm to simulate the hydrodynamics of the evolution of the free surface using a novel freesurface-capillary model, inspired by the molecular basis of surface tension. We present validations for the model and simulations of formation and rupture of liquid bridges.